Effect of the Grazing on the Sows’ Performance - Szendi, Róbert; Bodó, Imre; Nagy, Géze (Acta Agraria Debreceniensis, 2003)
Intensive indoor pig ptductiv technologies have entirely prevailed over the outdoor keeping of pigs. In Western Europe, sowgreasing is managed on a farm-size scale. In our experiment sows were grased during two grazing seasons, from April 28 to July 07, 2000, and from 14 September to December 10, 2000. The same number of indoor sows served as control animals. The results of the blood test show that, as a result of grazing, the beta carotene level of the blood serum has increased threefold. On spring pasture, the grasingsows gained 50 kg in weight as opposed to 30 kg in control animals. On the poor autumn pasture, the weight gained was only 30 kg, which was only 2 kg more in comparison with the performance of the control group. In both groups, loss in weight following the farrowing interval between the two grazing cycles was almost the same, that is, 47 kg. Thus, sows in the grased group were not worn at the end of the suckling period. The number of stillborn piglets in the grased groups of sows was three times smaller, and the piglets were 100 g heavier. Following the second grazing cycle, the litter of the experimental sows grew by 10%, there were fewer stillborn pigs, however, the average weight of the farrow was 140 g less.